Optimizing Ocular Vestibular Evoked Myogenic Potentials With Narrow Band CE-Chirps. Issue 5 (15th September 2021) - Mat, Quentin; Duterme, Jean-Pierre; Tainmont, Sophie; Lelubre, Christophe; Manto, Mario
Abstract : Objectives: To evaluate the effects of narrow band CE-Chirp (NB CE-Chirp) on the amplitudes and latencies in ocular vestibular evoked myogenic potentials (oVEMPs) at 500 and 1000 Hz in comparison with tone burst (TB). Design: Twenty-one healthy volunteers were included in the study and tested in air conduction with a "belly-tendon" montage. Recording conditions were randomized for each participant and each modality was tested twice to check the reproducibility of the procedure. Results: NB CE-Chirps at 500 Hz revealed larger n1-p1 amplitudes than 500 Hz TBs ( p = .001), which were also larger than NB CE-Chirps and TBs at 1000 Hz ( p = .022, p < .001, respectively). Besides, n1 and p1 latencies were shorter in NB CE-Chirp than in TB at 500 Hz ( p < .001) and 1000 Hz ( p < .001). The older the participants, the lower the amplitudes ( p = .021, p = .031) and the longer the n1 ( p = .030, p = .025) and p1 latencies ( p < .001, p < .001) in 500 Hz NB CE-Chirps and 500 Hz TBs. Interaural asymmetry ratios were slightly higher in 500 Hz NB CE-Chirps as compared to 500 Hz TBs ( p = .013). Conclusions: NB CE-Chirps at 500 Hz improved the amplitudes of waveforms in oVEMPs. As for TBs with clicks before, enhancing oVEMPs amplitudes is an essential step to distinguish a healthy person from a patient with either utricular or its related pathways disorder and potentially minimize the risk of cochlear damages. Additional studies including a higher number of healthy participants and patients with vestibular disorders are required to confirm this hypothesis. The large interindividual variability of interaural asymmetry ratios in NB CE-Chirp and in TB at 500 Hz could be explained by the selected montage.